Multi-tenant resource sharing with equitable-priority-based performance isolation of slices for 5G cellular systems - Yarkina, Natalia; Correia, Luis M.; Moltchanov, Dmitri; Gaidamaka, Yuliya; Samouylov, Konstantin (Computer communications, 2022)
Network slicing is a promising technique to enable multi-tenant operation in fifth generation (5G) cellular systems. However, efficient implementation of this technique at the air interface requires an adequate resource allocation policy that provides slice isolation and takes into account the heterogeneity of services and their performance requirements. We propose a new slicing scheme aimed at slice performance isolation, efficient capacity utilization, and fair resource allocation among all users. The policy ensures a slice-specific minimum data rate to all slice users as long as their number remains within a contracted limit, yet provides higher data rates whenever capacity is available. Specifically, we incorporate the best features of the complete partitioning and complete sharing policies, while ensuring flexibility and customization for network operators. The proposed scheme is based on an iterative solution of a convex programming problem characterized by polynomial complexity, which makes it suitable for on-line implementation. Associated algorithms are also proposed. Our numerical results demonstrate that the proposed slicing scheme is capable to accommodate heterogeneous traffic and provides performance isolation of slices while maintaining resource utilization at the level of complete sharing. Depending on the system parameters, the proposed scheme allows to improve session loss probability by an order of magnitude as compared to static slicing, while keeping the user data rates comparable to that of the complete sharing scheme and improving the average user satisfaction index by up to 90%. Overall, the proposed scheme results in efficient resource utilization compared to slicing policies in which slice isolation is provided via reservation by setting fixed upper or lower capacity bounds.